Draft Genomes of Two Strains of Flavobacterium Isolated from Lake Washington Sediment - McTaggart, Tami L. (Genome Announc, 2015)
We report sequencing the genomes of two new Flavobacterium strains isolated from Lake Washington sediment. From genomic contents, versatile lifestyles were predicted but not bona fide methylotrophy. With the availability of their genomic sequences, the new Flavobacterium strains present prospective models for studying microbial communities in lake sediments.